2007
DOI: 10.1080/03601230701735243
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine sorption by hydroxy-interlayered clays and their organic complexes

Abstract: This study examined the sorption of atrazine by hydroxy-Fe interlayered montmorillonite (FeMt) and its hydroquinone (FeMtHQ), citrate (FeMtCt) and catechol (FeMtCC) complexes as well as by hydroxy-Al interlayered montmorillonite (AlMt) and its hydroquinone (AlMtHQ) and citrate (AlMtCt) complexes. Found among the clays were sorption distribution coefficients (K(d)) ranging from 24 to 123 mL g(-1) and maximum sorption (M) ranging from 2.2 to 16.8 microg g(-1). Both K(d) and M decreased in the order of FeMtCC > F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…5). Similar conclusions were derived on biochar of pine needles by Chen et al (2008a,b), hydroxy-interlayered clays by Indraratne et al (2008) and activated carbons by Cao et al (2009). However, Cao et al (2009) found that little competition occurred between Pb and atrazine for sorption on dairy-mature derived biochar, because precipitation as Pb 9 (PO 4 ) 6 or Pb 3 (CO 3 ) 2 (OH) 2 and partitioning were respectively responsible for Pb and atrazine sorption there (Cao et al, 2009(Cao et al, , 2011.…”
Section: Interactive Influence With the Coexisting Pb(ii) And Cr(vi) supporting
confidence: 75%
“…5). Similar conclusions were derived on biochar of pine needles by Chen et al (2008a,b), hydroxy-interlayered clays by Indraratne et al (2008) and activated carbons by Cao et al (2009). However, Cao et al (2009) found that little competition occurred between Pb and atrazine for sorption on dairy-mature derived biochar, because precipitation as Pb 9 (PO 4 ) 6 or Pb 3 (CO 3 ) 2 (OH) 2 and partitioning were respectively responsible for Pb and atrazine sorption there (Cao et al, 2009(Cao et al, , 2011.…”
Section: Interactive Influence With the Coexisting Pb(ii) And Cr(vi) supporting
confidence: 75%
“…which are the key environmental factors for atrazine degradation (Hickman and Reid, 2008;Indraratne et al, 2008;Wang et al, 2011). The acid dissociation constant (pKa) of atrazine is 1.68, and the ionized atrazine fraction therefore increases at higher soil pH and principally raises atrazine availability to microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The feature consisted of local ceramics with special assemblage with clay figurines, quartz querns, and biotite muscovite schist grinders [23]. An iron razor blade was recovered with the clay suggesting a causal linkage with some medical implications since the use of natural clay for cell growth and treatment of diseases has been extensively documented [24][25][26][27][28]. There are ethnographic parallels to the use of the clay in treating related ailments including fractured bones in Yikpabongo in the Northern Region of Ghana.…”
Section: Introductionmentioning
confidence: 99%